Integration of Traditional Agricultural Systems with the Concept of Sustainable Agriculture: Opportunities and Challenges - Kamakaula, Yohanes; Palinggi, Yunita; Pattiasina, Trees A. (West Science Nature and Technology, 2024)
Traditional agriculture has long been an integral part of agrarian systems in various regions, yet global challenges such as climate change and urbanization demand more sustainable approaches. This study aims to explore the opportunities and challenges of integrating traditional agricultural systems with sustainable agriculture concepts through a literature review method. The findings reveal that traditional practices, such as crop rotation and organic fertilization, align with sustainability principles. However, there is a need to enhance efficiency through the application of modern technologies such as precision irrigation and integrated pest management. This integration faces significant challenges, including farmers' limited access to technology and a lack of supportive policies. The study highlights the importance of contextual approaches, farmer training, and cross-sector collaboration to optimize the potential of this integration. Thus, the findings provide relevant insights for developing sustainable agricultural policies and practices in Indonesia and other countries.